Delineating the continuum of marine ecosystem-based management: a US fisheries reference point perspective. (28th December 2015) - Dolan, Tara E.; Patrick, Wesley S.; Link, Jason S.
Abstract: Ecosystem management (EM) suffers from linguistic uncertainty surrounding the definition of "EM" and how it can be operationalized. Using fisheries management as an example, we clarify how EM exists in different paradigms along a continuum, starting with a single-species focus and building towards a more systemic and multi-sector perspective. Focusing on the specification of biological and other systemic reference points (SRPs) used in each paradigm and its related regulatory and governance structures, we compare and contrast similarities among these paradigms. We find that although EM is a hierarchical continuum, similar SRPs can be used throughout the continuum, but the scope of these reference points are broader at higher levels of management. This work interprets the current state of the conversation, and may help to clarify the levels of how EM is applied now and how it can be applied in the future, further advancing its implementation.